'The Nowness of Everything': A mindfulness-based approach to psychotherapy. Issue 1 (2nd January 2016) - MacDonald, Pat
Abstract : Current levels of mental distress are of great concern to those of us working in the therapeutic setting. Many people today are discontented and unhappy with their lives. Success fails to bring fulfilment and with alienation from self and others, an inner numbness can become established. When working with troubled individuals or participants of groups, I believe by remaining with a mindfulness-based here-and-now approach, levels of depression, anxiety, narcissistic conceit and acquisitiveness become diminished. At the same time, I feel peace of mind increases when in-the-moment experiences are the focus of attention. It would seem that a mindful approach which involves circumventing client history and concentrating on current feelings and experiences can effectively facilitate psychic change. This paper considers some of the literature of mindfulness, in an attempt to validate my observations and determine if there is a satisfactory evidence base for a mindfulness-based psychotherapeutic approach to the ills of contemporary life.